ENT 300 Butterfly Cake Bussiness Plan / Janet Victoria anak Stia... [et.al] - Stia, Janet Victoria; Urang, Beathrice Teladik; Mawang, Jazelina Intan; Dhelbi, Jacqueline Wena; Abd Rahman, Awanis (2020)
Ice cream cakes are still not common in our community. Only few cake houses offer ice cream cakes but not so significant. By viewing this potential, we try our best in venturing into this ice cream cakes production. From the survey and research we have done, potential in this business is big due to the demand from the community especially the teenagers. For the opening of our business, we offer 5 all favourite tastes that are Choc-A-Lot, Strawberry, Tiramisu, Oreo and Black forest. The other two are the Malaysian taste: Honey and Date Cheese and Durian Cheese. All are combined with ice cream to produce the ice cream cakes. Our target market is big ranging from youngsters to adult as long as they love the ice cream cakes. Anybody who is interested in using ice cream cakes in their birthday, wedding or any events can try our products. We have our own method to sustain the ice cream cakes. From tourists, visitors to locals everybody can enjoy our ice cream cakes. It is Halal guaranteed.From this situation we expect big returns to our initial cost.